Diastereoselective synthesis of new O-alkylated and C-branched inositols and their corresponding fluoro analogues - Collet, Charlotte; Chrétien, Françoise; Chapleur, Yves; Lamandé-Langle, Sandrine (Beilstein Journal of Organic Chemistry, 2016)
Efficient routes were developed for the diastereoselective synthesis of new O-alkylated and C-branched inositols and their corresponding fluoro analogues. The key steps of the synthesis were the easy accessibility of different types of arms in term of configuration (myo and scyllo), the linking method and length, which could modulate the biological properties. These inositol derivatives, bearing an arm terminated either with a hydroxy group or a fluorine atom, could be interesting candidates for diastereoisomeric intermediates and biological evaluations, especially for PET imaging experiments.
Keywords: C-branched; diastereoselective; fluoroinositols; inositols; O-alkylated